2016
DOI: 10.1002/admi.201500768
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Planar Perovskite Solar Cells Produced from PbI2(DMSO) and PbI2(NMP) Complexes by Intramolecular Exchange

Abstract: intermediate phase is another very effective way to transfer a uniform and high-quality perovskite fi lm because the intermediate phase can slow down the reaction between PbI 2 and FAI in solution. [ 27 ] Recently, intramolecular exchange has been shown to dramatically improve the power conversion effi ciency of perovskite solar cells (PSCs), and such exchange of DMSO intercalated in PbI 2 (PbI 2 (DMSO) complex) with FAI leads to crystallization of FAPbI 3 because FAI has a higher affi nity for PbI 2 than does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(135 citation statements)
references
References 35 publications
5
130
0
Order By: Relevance
“…[35] Thus, complex-forming solvents can be used to "pre-stretch" the PbI 2 lattice for the organic compounds that are incorporated into the structure via a molecule exchange reaction. [36] An example of this is depicted for DMSO and NMP in Figure 2b.…”
Section: Crystallization Through Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Thus, complex-forming solvents can be used to "pre-stretch" the PbI 2 lattice for the organic compounds that are incorporated into the structure via a molecule exchange reaction. [36] An example of this is depicted for DMSO and NMP in Figure 2b.…”
Section: Crystallization Through Complex Formationmentioning
confidence: 99%
“…[36,38,39] So-called polar aprotic solvents, implying solvents with functional groups containing oxygen (O), sulphur (S), or nitrogen (N), can act as Lewis bases in the vicinity of the Lewis acid PbI 2 . They can be classified into O-donors, like DMSO, NMP, or Figure 1.…”
Section: Crystallization Through Complex Formationmentioning
confidence: 99%
“…The field is indeed dominated by the HTM 2,2´,7,7´-tetrakis(N,N-di-pmethoxyphenylamine)-9,9´-spirobifluorene (spiro-OMeTAD) and by the even more expensive poly[bis(4-phenyl)-(2,4,6-trimethylphenyl)amine] (PTAA). [13,14] Developing new HTM molecules through inexpensive synthetic routes and without needing of tedious purification steps remains therefore as a primary goal. Finding HTMs that exhibit holeinjection and transport properties similar to spiro-OMeTAD and PTAA, and closely match the valence band edge of the perovskite is the key for avoiding any loss in electrical potential and charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Details of these procedures are discussed in Section . It has been shown that it is advantageous to use strongly coordinating Lewis base solvents such as DMSO and NMP for PbI 2 deposition, as this results in PbI 2 ‐solvent adducts that can be converted into perovskites by intramolecular exchange when exposed to the monovalent cation, forming large uniform crystals in the process . For IJP, the results suggest that a two‐step conversion process is most suitable on mesoporous contact layers, as this improves pore‐filling and surface coverage .…”
Section: From Perovskite Ink To Printed Nanocrystals Wires and Thinmentioning
confidence: 99%